Bruchid Infestation in Pod and Seed in Exotic Collections of Acacia senegal (L.) Willd. in the Thar Desert - Patel, Nisha; Jindal, S K; singh, Manjit; Pancholy, Anjly (Annals of Arid Zone, 2016)
Exotic germplasm of Acacia senegal coJlected from the forests of Niger, Mali and Senegal were transplanted in 1988, and evaluated for tree morphology, pod and seed yield related traits for two years during 2005 and 2006. Mean values in 2006 were 7.33 cm for pod length, 4.71 kg for pod yield per tree, 3.87 for number of seeds per infested pod and 3.79 for number of seedslhealthy pod, which were significantly higher than those of 2005. On the other hand mean values were 24.9 for sheJling percentage, 8.0% for pod infestation and 3.33 for percent of seeds infested in healthy pods, which were significantly lower than the values of 2005. Two species of bruchids, i.e. Bruchus bilineatopygus Pic. and Caryedon serratus Olivier were found to infest the seeds. EC87/7490, the highest pod and seed yielder with minimum seed infestation, was found to have more than 30% survival. Therefore the seeds of this accession can be used directly for large-scale plantation. Key words: Acacia senegal. seed yield, bruchids, seed and pod infestation, exotic material